Genetic insights into number of long-term conditions and their relationship with lifespan - Youngjune Bhak; Bruce Guthrie; Albert Tenesa (PLoS ONE, 2026)
Aims Relationships between the genetic risk for long-term conditions (LTCs) and lifespan have been reported. However, the genetic factors underlying the total number of LTCs an individual has (LTC burden) and their association with lifespan have not been fully investigated. This study aims to investigate the genetics of LTC burden and evaluate its relationship with lifespan. Methods A genome-wide association study (GWAS) and a genetic heritability test were conducted on LTC burden using data from 343,868 UK Biobank individuals. Global and local genetic correlations between the LTC burden and parental lifespan were estimated. A polygenic risk score (PRS LTC ) for LTC burden was derived from a separate set of 34,339 UK Biobank individuals with records of age at death, who were not included in the GWAS analysis. The association between the PRS LTC and lifespan, as well as its ability to predict LTC burden, was assessed. Results Loci in the HLA region were the most significant among the 21 significant independent loci from the GWAS. The estimated SNP heritability of LTC burden was 0.0963 and significantly different from zero (se = 0.0034, p-value = 1.77 x 10 −176 ). The global genetic correlation between LTC burden and parental lifespan exhibited a significant global genetic correlation of −0.7869 (se = 0.0419, p-value 9.57 x 10 −79 ). Additionally, 44 loci showed significant local genetic correlations (p-value < 2.23 x 10 −5 ). Individuals in the highest 10% PRS LTC had, on average, a 0.9-year shorter lifespan and 0.73 more LTCs than those in the lowest 10%. Conclusions This study identifies significant genetic factors associated with LTC burden and their association with lifespan, providing insights into the genetic underpinnings of both multiple LTCs and lifespan.